2012
DOI: 10.1124/jpet.112.194639
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of a Mutant Cocaine Esterase: Effects on Plasma Cocaine Levels, Cocaine-Induced Cardiovascular Activity, and Immune Responses in Rhesus Monkeys

Abstract: Previous studies have demonstrated the capacity of a longacting mutant form of a naturally occurring bacterial double mutant cocaine esterase (DM CocE) to antagonize the reinforcing, discriminative, convulsant, and lethal effects of cocaine in rodents and reverse the increases in mean arterial pressure (MAP) and heart rate (HR) produced by cocaine in rhesus monkeys. This study was aimed at characterizing the immunologic responses to repeated dosing with DM CocE and determining whether the development of anti-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
1
12
0
2
Order By: Relevance
“…Impedance-based measurement of respiratory function has been extensively described in humans, and the approach of combined cardiopulmonary assessments has been validated in monkeys (56). The basal values of these physiological parameters in this study are in line with those reported in rhesus monkeys (40,52,54). BU08028 at antinociceptive doses and ∼10-to 30-fold higher doses did not cause significantly respiratory depression or adverse cardiovascular events, whereas fentanyl produced a rapid, severe decrease in respiratory rate.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Impedance-based measurement of respiratory function has been extensively described in humans, and the approach of combined cardiopulmonary assessments has been validated in monkeys (56). The basal values of these physiological parameters in this study are in line with those reported in rhesus monkeys (40,52,54). BU08028 at antinociceptive doses and ∼10-to 30-fold higher doses did not cause significantly respiratory depression or adverse cardiovascular events, whereas fentanyl produced a rapid, severe decrease in respiratory rate.…”
Section: Discussionsupporting
confidence: 77%
“…To characterize the safety profile of BU08028, we implanted radiotelemetric transmitters in monkeys for real-time measurements of different physiological functions (52). A systemic dose (0.01 mg/kg) of BU08028 that produced full antinociceptive effects did not significantly affect the respiratory function of freely moving monkeys, i.e., no respiratory depression ( Fig.…”
Section: Bu08028 Produces Potent and Long-lasting Antinociceptive Andmentioning
confidence: 99%
“…Plasma was collected in polypropylene tubes containing 20 ml of a solution of 1 mg/ml sodium fluoride and 60% acetic acid and then stored at 280°C. Pharmacokinetic procedures were based on previous studies in which plasma cocaine levels were assessed in rhesus monkeys (Collins et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…However, an immune response was noted with repeated administrations of CocE, and as antiCocE antibodies increased, the clinical response to treatment declined (Ko et al, 2009). Double mutant CocE (T172R/ G173Q) given to rhesus monkeys 10 minutes after cocaine improved mean arterial pressure, heart rate, and locomotor activity, even as anti-double mutant CocE antibody titers increased in the animals after repeated administrations (Collins et al, 2011(Collins et al, , 2012. Effective enzymatic therapy for acute cocaine toxicity has the potential to be curative, although significant caveats to its administration will apply.…”
Section: Pharmacokinetic Approachesmentioning
confidence: 99%